A Standardized Plaque Reduction Assay for Determination of Drug Susceptibilities of Cytomegalovirus Clinical Isolates - Landry, Marie L. (American Society for Microbiology, 2000)
Twelve laboratories collaborated in formulating and testing a standardized plaque reduction assay for cytomegalovirus (CMV) cell-associated clinical isolates. Four characterized and plaque-purified CMV strains, as well as six coded clinical isolates obtained after antiviral therapy, were distributed and tested. Good agreement was obtained for four of the clinical isolates, but a broad distribution of results was obtained for two isolates. Analysis of these results indicates the problems associated with clinical isolates, including the large genetic variability and the highly cell-associated phenotype. This collaborative effort, by addressing these problems, represents a significant step toward the development of a standardized assay.